Comparative Study of Attitude Assessment Between Senior High School and Vocational High School - Bayu Ananto Wibowo (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Character education which is the main focus of the 2013 curriculum makes teachers not only fixated on cognitive assessment, but also required to give an affective assessment. In practice, the assessment of attitudes at the Senior High School and Vocational High School levels has differences in terms of the assessment instrument and the assessment process. This study aims to determine, (1) Attitude assessment conducted at the Senior High School level, (2) Attitude assessment conducted by Vocational High School, (3) To determine the comparison of attitude assessments between Senior High School and Vocational High School. Data retrieval in this study was carried Senior high schools at Yogyakarta and Vocational High School at Yogyakarta.